Analysis of Students' Cognitive, Affective and Psychomotor Aspects of Accounting Materials as an Information System Subject of Service Company Accounting Cycle - Dedi Irawan Zebua (Universitas Muhammadiyah Enrekang, 2022)
This study aims to find out how the level of cognitive, affective and psychomotor abilities of students in learning accounting material as an information system by class XI students of Christian Private Vocational Schools BNKP Gunungsitoli. This type of research is research. The type of data used is a type of quantitative data and the data is obtained by carrying out learning achievement tests on students. The sample in this study were 21 students of class XI at Christian Private Vocational School BNKP Gunungsitoli. To determine the level of affective and psychomotor abilities used observation tables. From the results of the research conducted, it was found that overall students' cognitive abilities in accounting material as an information system were classified as Good material mastery category (71.83%) with a low level of difficulty (28.17%). The level of students' affective abilities is categorized as Good with a score of (74) while the level of students' psychomotor abilities is categorized as skilled with an acquisition of a score (72).